Does Envy Destroy Social Fundamentals? The Impact of Relative Income Position on Social Capital - Justina A.V. Fischer; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
Research evidence on the impact of relative income position on individual attitudes and behaviour is sorely lacking. Therefore, this paper assesses such positional impact on social capital by applying 14 different measurements to International Social Survey Programme data from 25 countries. We find support for a positional concern effect or ?envy? whose magnitude in several cases is quite substantial. The results indicate that such an effect is non-linear. In addition, we find an indication that absolute income level is also relevant. Lastly, changing the reference group (regional versus national) produces no significant differences in the results.
Keywords: Z13; H26; I31; D00; D60; 330; Relative income position; envy; positional concerns; social capital; social norms; happiness